2016
DOI: 10.1039/c5fo01285f
|View full text |Cite
|
Sign up to set email alerts
|

Food structure is critical for optimal health

Abstract: Much nutrition policy is nutrient-based, supported by extensive nutrient science and food nutrient composition tables and recommendations for dietary evaluation. There are no comparable instruments for food structure. This constitutes a policy and practice gap since food is valued for its textural properties and not simply its chemistry. The structurally-important 'dietary fibre' at first proved of greater interest for its chemistry than its physico-chemistry even to health scientists and workers. As food chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…The spatial arrangement of food constituents (food structure) is notably determined by food processing and regulates digestion mostly through modifications of the accessibility of digestive enzymes . Food structure has been mostly studied by in vitro digestion, however, few in vivo published studies showed that food structure may regulate transit time, nutrient sensing and absorption in the gastrointestinal tract as well as satiety and post‐prandial metabolism . For instance, in humans a coarse fat emulsion delivered intra‐gastrically, decreased lipolysis in the duodenum relatively to a fine fat emulsion .…”
Section: Introductionmentioning
confidence: 99%
“…The spatial arrangement of food constituents (food structure) is notably determined by food processing and regulates digestion mostly through modifications of the accessibility of digestive enzymes . Food structure has been mostly studied by in vitro digestion, however, few in vivo published studies showed that food structure may regulate transit time, nutrient sensing and absorption in the gastrointestinal tract as well as satiety and post‐prandial metabolism . For instance, in humans a coarse fat emulsion delivered intra‐gastrically, decreased lipolysis in the duodenum relatively to a fine fat emulsion .…”
Section: Introductionmentioning
confidence: 99%
“…Food processing, which ranges from minimal to extensive processing, is defined as any procedure that alters food from its natural state ( 1 ). Food processing may affect patterns of purchase, use, and consumption as well as nutritional quality (including structure), affordability, and sustainability ( 2 ). Degree of processing has health implications arising from the lack of health protective food components like dietary fiber with decreased nutrient density; the greater presence of factors that are health adverse such as sodium, saturated and trans fatty acids, and contaminants including endocrine disruptors; and increased energy density ( 3 , 4 ).…”
mentioning
confidence: 99%
“…The food matrix is based on structural capacities of foods, in which macro and micronutrients are offered. This food structure makes the difference between biological and health outcomes [29]. Food synergy is based on the proposition that the interrelations between constituents in foods are important, as well as the interactions between foods, and that the total effect on health is greater than just the sum of all individual effects [14].…”
Section: Discussionmentioning
confidence: 99%